2023
DOI: 10.1080/22221751.2023.2178238
|View full text |Cite
|
Sign up to set email alerts
|

NSUN2-mediated m 5 C methylation of IRF3 mRNA negatively regulates type I interferon responses during various viral infections

Abstract: 5-Methylcytosine (m 5 C) is a widespread post-transcriptional RNA modification and is reported to be involved in manifold cellular responses and biological processes through regulating RNA metabolism. However, its regulatory role in antiviral innate immunity has not yet been elucidated. Here, we report that NSUN2, a typical m 5 C methyltransferase, negatively regulates type I interferon responses during various viral infections, including SARS-CoV-2. NSUN2 specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…For EBV infection, NSUN2 catalyzes the m5C modification of EBER1, which impacts its metabolism and defense against the virus ( 102 ). Flaviviruses ( 103 ), hepatitis C virus (HCV) ( 104 ), Dengue Virus (DENV) ( 105 ), Zika Virus (ZIKV) ( 103 ) and others regulated by NSUN2; the methyl donor inhibitor A9145 has been found to inhibit the replication of DENV and ZIKV ( 105 ). It has been reported that the knockdown of NSUN2 does not significantly alter the m5C methylation of viral RNAs, but reduces the replication and gene expression of a variety of viruses (RSV, VSV, hMPV, SeV, and HSV) ( 22 ).…”
Section: Potential Role Of M5c Methylation In Regulating Sars-cov-2 I...mentioning
confidence: 99%
See 4 more Smart Citations
“…For EBV infection, NSUN2 catalyzes the m5C modification of EBER1, which impacts its metabolism and defense against the virus ( 102 ). Flaviviruses ( 103 ), hepatitis C virus (HCV) ( 104 ), Dengue Virus (DENV) ( 105 ), Zika Virus (ZIKV) ( 103 ) and others regulated by NSUN2; the methyl donor inhibitor A9145 has been found to inhibit the replication of DENV and ZIKV ( 105 ). It has been reported that the knockdown of NSUN2 does not significantly alter the m5C methylation of viral RNAs, but reduces the replication and gene expression of a variety of viruses (RSV, VSV, hMPV, SeV, and HSV) ( 22 ).…”
Section: Potential Role Of M5c Methylation In Regulating Sars-cov-2 I...mentioning
confidence: 99%
“…Through transcriptome sequencing of RNA isolated from bronchoalveolar lavage fluid (BALF) of two SARS-CoV-2 patients, NSUN2 mRNA level is found decreased in SARS-CoV-2 patients compared with that in healthy individuals. In comparison to the uninfected group, the infected mice with the SARS-CoV-2 WT strain or the K18-hACE2 KI mouse model with BA.1 omicron variant-activated innate immune response show significantly lower endogenous NSUN2 mRNA levels ( 103 ). These results could be also observed in the SARS-CoV-2-infected Caco-2 cell model and SARS-CoV-2 patients, suggesting that NSUN2 plays an important regulatory role in SARS-CoV-2 infection.…”
Section: Potential Role Of M5c Methylation In Regulating Sars-cov-2 I...mentioning
confidence: 99%
See 3 more Smart Citations